Organizacja szkolnictwa polskiego w Bydgoszczy po 1918 roku (Tabularium Historiae, 2020)
The subject of the article concerns the processes of organizing Polish education in Bydgoszcz at the end of the Prussian rule in the city. The initiatives of the emerging Polish educational institutions and national activists aimed at taking over education from the Prussian administration were shown. Individual schools were presented, with particular emphasis on secondary schools, which were incorporated into the Polish educational system after Bydgoszcz returned to Poland in January 1920.